2020
DOI: 10.3390/ijms21051717
|View full text |Cite
|
Sign up to set email alerts
|

Rosa davurica Pall. Improves Propionibacterium acnes-Induced Inflammatory Responses in Mouse Ear Edema Model and Suppresses Pro-Inflammatory Chemokine Production via MAPK and NF-κB Pathways in HaCaT Cells

Abstract: Acne, also known as acne vulgaris, is a common disorder of human skin involving the sebaceous gland and Propionibacterium acnes (P. acnes). Although there are a number of treatments suggested for acne, many of them have limitations in their safety and have efficacy issues. Therefore, there is a high demand to develop safe and effective novel acne treatments. In the present study, we demonstrate the protective effects of Rosa davurica Pall. leaves (RDL) extract against P. acnes-induced inflammatory responses in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Thus, we concluded that SMYEE might be a safe and effective acne treatment. We evaluated the effects of SMYEE on the C. acnes-induced inflammatory response in vivo using a well-known mouse acne model; the lesions are similar to those of humans [26]. C. acnes injection into mouse dorsal skin induces nodule development, swelling, redness, erythema, epidermal hyperplasia and thickening, as well as the accumulation of inflammatory cells (especially neutrophils).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we concluded that SMYEE might be a safe and effective acne treatment. We evaluated the effects of SMYEE on the C. acnes-induced inflammatory response in vivo using a well-known mouse acne model; the lesions are similar to those of humans [26]. C. acnes injection into mouse dorsal skin induces nodule development, swelling, redness, erythema, epidermal hyperplasia and thickening, as well as the accumulation of inflammatory cells (especially neutrophils).…”
Section: Discussionmentioning
confidence: 99%
“…Since many previous studies have reported that activation of NF-κB and MAPK signaling pathways is involved in TNF-α-induced expression of proinflammatory mediators in keratinocytes (Razali et al 2018 ; Sikandan et al 2018 ; Hwang et al 2020 ), we further examined the effect of FB801 on TNF-α-induced IκB-α degradation and phosphorylation of MAPK by Western blot analysis. Stimulation of HaCaT cells with TNF-α (10 ng/mL, 15 min) rapidly induced IκB-α degradation and MAPK phosphorylation, as shown in Figure 6 .…”
Section: Resultsmentioning
confidence: 99%
“…The inflammatory response induced by C. acnes is mediated by the pattern recognition receptor Toll-like receptor-2 (TLR2) expressed in keratinocytes and APCs [ 47 ]. In vitro studies demonstrated that upon the C. acnes challenge, the mitogen-activated protein kinase (MAPK) and nuclear factor-kB (NF-kB) pathways are activated leading to the production of TNF-α, IL-8, IL-6, and IL-1β by HaCaT cells [ 48 ] and THP-1 macrophages [ 49 ]. In line with those findings, it was shown that the C. acnes -induced inflammatory response promotes the accumulation of neutrophils [ 50 ] and lymphocytes [ 51 ] in the sebaceous follicles, where they can promote the breakdown of the follicular wall, stimulating further inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In order to demonstrate the potential beneficial effects of orally administered W. viridescens UCO-SMC3, we next used a mice model of acne for in vivo studies. Most of the studies using mice to evaluate C. acnes infection usually inject the pathogen into the animal’s ears [ 48 , 62 , 63 ]. C. acnes inoculated subcutaneously into the back of the ears induce ear swelling, redness, and erythema [ 48 ], which are associated with the local and systemic production of TNF-α, IL-6, and IL-8 [ 63 ] as well as the infiltration of CD45 + Ly6G + neutrophils and CD45 + F4/80 + macrophages into the infected tissue [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation